중년여성의 자아정체감과 삶의 이유 간의 관계에서 부부관계 만족도와 우울의 매개효과 - 박희숙(Hee-Sook Park); 정구철(Goo-Churl Jeong) (한국콘텐츠학회 논문지, 20(1), 2020)
This study was conducted to examine the mediating effects of marital satisfaction and depression on the relationship between self-identity and reasons for living in middle-aged women. For this, a survey was conducted on 200 middle-aged women. As a result, first, there was a significant positive correlation between self-identity, marital satisfaction, depression, and reasons for living. Second, the marital satisfaction had a significant mediating effect on the relationship between self-identity and the reasons for living of middle-aged women. Third, depression had a significant mediating effect on the relationship between self-identity and reasons for living. Fourth, the multiple mediating effect of marital satisfaction and depression was statistically significant in the relationship between self-identity and reasons for living in middle-aged women. Based on these results, we discussed the importance of the self-identity of middle-aged women and the role of spouses as significant other partners, and suggested ways to overcome the crisis of middle-aged women. 본 연구는 중년여성들을 대상으로 자아정체감과 삶의 이유 간의 관계에서 부부관계 만족도와 우울의 매개효과를 검증하기 위해 수행되었다. 이를 위해 중년여성 200명을 대상으로 설문조사를 수행하였다. 연구결과, 첫째, 자아정체감, 부부관계 만족도, 우울 및 삶의 이유 간에 모두 유의한 정적 상관관계가 나타났다. 둘째, 중년여성의 자아정체감과 삶의 이유 간의 관계에서 부부관계 만족도는 유의한 매개효과가 있었다. 셋째, 자아정체감과 삶의 이유간의 관계에서 우울은 유의한 매개효과가 있었다. 넷째, 중년여성의 자아정체감과 삶의 이유 간의 관계에서 부부관계 만족도와 우울을 통한 이중 매개효과는 통계적으로 유의하였다. 이러한 연구결과를 바탕으로 중년여성의 자아정체감 형성의 중요성과 중요한 타자로서의 배우자 역할에 대해 논의하였으며, 중년여성의 위기감 극복을 위한 방안들을 제언하였다.